Legal Implications of Foreign Investment Relating to Technology Transfer in the Patent Regime - Labetubun, Muchtar Anshary Hamid; Akyuwen, Rory Jeff; Narwadan, Theresia Nolda Agnes (SASI, 2022)
Introduction: The issue of technology transfer is a problem that is always faced by developing countries, including Indonesia. Since Indonesia has directed its economic development by focusing on the industrial sector, until the industrial sector has become the backbone of the national economy.Purposes of the Research: forms of technology transfer in investment and procedures for technology transfer in investment activities in Indonesia.Methods of the Research: the method used in this research is normative juridical to analyze the legal problems contained in the legislation releted to the problem under study with a qualitative analysis.Results of the Research: the results shown that foreign investment and technology transfer are in inseparable pair. Technology transfer or often reffered to as technology transfer includes, product, production processes and machinery. The technology transfer procedure can be transferred by employing individual foreign experts, providing supplies of machines and other equipment. Legal implication in technology transfer can occur in various forms, such as licensing agreements in technology, technology owners can facilitate technology by giving rights to each person/entity to implement technology with a license, expertise and technology assistance.